Equity Trading Volume and its Relationship with Market Volatility: Evidence from Indian Equity Market - Naik, Pramod Kumar; Padhi, Puja (Journal of Asian Business Strategy, 2014)
This study investigates stock market volatility asymmetry and its relationship with equity trading volume in the Indian stock market using daily data over the period from 2nd January 1997 to 30th May 2013. We employ GARCH, EGARCH and GJR-GARCH models to examine the volatility pattern in the stock market. We also decompose the conditional variance into a transitory and permanent component, modeled by asymmetric CGARCH, in order to check the short run and long run movements of volatility. Further, contemporaneous trading volumes are augmented in the volatility model to empirically verify the validity of Mixture of Distribution Hypothesis (MDH) and the level of volatility persistence. The findings show significant volatility asymmetry in the Indian equity market, supporting the leverage effect hypothesis. Secondly, we find a positive contemporaneous relationship between volume and volatility, validating the argument of MDH. Moreover, the results show that the volatility shocks are highly persistent even after incorporating trading volume, contradicting the seminal findings of Lamoureux and Lastrapes (1990).